2018
DOI: 10.1039/c8ra08532c
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and magnetic properties of undoped and copper-doped cobalt ferrite nanoparticles prepared by the octanoate coprecipitation route at very low dopant concentrations

Abstract: Low level copper-doped CoFe2O4 has been synthesized and shows an increasing of saturation magnetization up to 6% Cu, subsequently decreasing above 6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 75 publications
(117 reference statements)
0
34
0
Order By: Relevance
“…A simple strategy was developed by Wang et al [98], which consists of microwave-assisted coprecipitation of ferrous sulphate in a mixture of ethylene glycol and water, affording nanosheets with good crystallinity and saturation magnetization around 30 emu/g. Zhuang et al [99] were able to synthesize magnetite nanosheets through a solvothermal method using diethylene glycol, which, through the inhibition of the crystal plane (111), favours the formation of magnetite sheet-like crystals. Furthermore, the authors demonstrated that the nanoparticles self-assemble into chain-like structures along the direction of the external magnetic field, known as photonic crystals, which display a magnetochromatic property.…”
Section: Nano-films Sheets and Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple strategy was developed by Wang et al [98], which consists of microwave-assisted coprecipitation of ferrous sulphate in a mixture of ethylene glycol and water, affording nanosheets with good crystallinity and saturation magnetization around 30 emu/g. Zhuang et al [99] were able to synthesize magnetite nanosheets through a solvothermal method using diethylene glycol, which, through the inhibition of the crystal plane (111), favours the formation of magnetite sheet-like crystals. Furthermore, the authors demonstrated that the nanoparticles self-assemble into chain-like structures along the direction of the external magnetic field, known as photonic crystals, which display a magnetochromatic property.…”
Section: Nano-films Sheets and Platesmentioning
confidence: 99%
“…Recently, Xu et al [110] were able to synthesize ultra-thin triangular magnetite nanoplates through a seed-mediated synthesis, where the seeds were obtained through the thermal decomposition of ferric oleate complex at 310 • C, and a growth-step (replenished with monomers) was carried out at a temperature (240 • C) lower than the required for nucleation (310 • C), but higher than the thermal decomposition of the complex (230 • C). Recently, the synthesis of Co 1-x Cu x Fe 2 O 4 has been achieved through a two-step synthesis, starting with coprecipitation of the metal salts in the right ratio, which dried powder was subjected to thermal decomposition in air at 400 • C in a tubular furnace [111]. Mn x Fe 1-x O nanoplates has also been recently reported, which are of biomedical interest owing to the resistance to oxidation in air compared to MnO and FeO, making them good candidates for magnetic contrast agents [112].…”
Section: Nano-films Sheets and Platesmentioning
confidence: 99%
“…However, when x = 0.1, the copper ion present in the tetrahedral site has the lowest coercivity and highest value of magnetocrystalline anisotropy constant, which may be attributed to Jahn-Teller distortions induced by Cu 2+ ions in the spinel ferrite system [52,54,56]. The squareness ratio (SQR) was calculated using the given formula [57]:…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The saturation magnetization, M s for all the compositions was obtained from the plot of M versus 1/H, for high H values, and extrapolating to 1/H = 0 (electronic supplementary material, figure S3) [38,39] It is observed that Co-substitution in NdFeO 3 greatly decreases the magnetization, coercive field, H c and remanent magnetization, M R . From the graph, the saturation magnetization of NdFeO 3 is 1.43 emu g −1 .…”
Section: Magnetic Properties By Vibrating Sample Magnetometermentioning
confidence: 99%